2017
DOI: 10.5897/jahr2017.0445
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus clustering patterns among HIV-infected and HIV-uninfected adolescent females in South Africa

Abstract: The global burden of disease caused by both human immunodeficiency virus (HIV) and human papillomavirus (HPV) is the greatest in the developing world, with the highest rates in sub-Saharan Africa. South African women not only have high rates of infection with HPV, but also have high rates of multiple concurrent infections with two or more HPV genotypes, and are among the world’s most vulnerable to developing invasive cervical cancer. HIV co-infection increases these risks. Understanding clustering patterns of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Most studies of HPV infection among sub-Saharan African women have been cross-sectional, indicating that HR- and LR-HPV infections are common and that HIV-infected women have a higher rate of HPV detection compared to HIV-uninfected women. 41 46 This study confirmed that all types of HPV are common and detected more often in HIV-infected Kenyan women than in HIV-uninfected women. Most importantly, persistence of all groups of HPV (any HPV, HR-HPV, IARC HR-HPV types, and LR-HPV types) was associated with HIV infection.…”
Section: Discussionsupporting
confidence: 73%
“…Most studies of HPV infection among sub-Saharan African women have been cross-sectional, indicating that HR- and LR-HPV infections are common and that HIV-infected women have a higher rate of HPV detection compared to HIV-uninfected women. 41 46 This study confirmed that all types of HPV are common and detected more often in HIV-infected Kenyan women than in HIV-uninfected women. Most importantly, persistence of all groups of HPV (any HPV, HR-HPV, IARC HR-HPV types, and LR-HPV types) was associated with HIV infection.…”
Section: Discussionsupporting
confidence: 73%
“…De-identified vaginal swabs from the University of Cape Town HPV-HIV study [33] were retrospectively used for bacteriome and virome analysis. This cohort was comprised of 50 HIVpositive and 50 HIV-negative young, sexually active women between the ages of 16 and 21 recruited from the youth community center and clinic in two urban disadvantaged communities (Masiphumelele and Mthatha townships) in Cape Town, South Africa between October 2012 and October 2014.…”
Section: Study Cohortmentioning
confidence: 99%
“…Vaginal swabs were self-collected approximately every 6 months by subjects using Dacron swabs high within the vagina, placed in Digene transport media, and frozen at -80°C until use. Pap smears were taken at baseline and at least one other visit, and tests for HPV, Trichomonas, and BV performed [33]. HIV status was confirmed upon enrollment, and CD4+ T cell count for those who were HIV-positive was determined.…”
Section: Study Cohortmentioning
confidence: 99%
See 2 more Smart Citations